Drivers of Ecological and Evolutionary Disruptions in the Seed Dispersal Process: Research Trends and Biases - Donoso, Isabel; Fricke, Evan C.; Hervías-Parejo, Sandra; Rogers, Haldre S.; Traveset, Anna (Frontiers in Ecology and Evolution, 2022)
As the sole opportunity for most plants to move, seed dispersal influences the biodiversity and functioning of plant communities. Global change drivers have the potential to disrupt seed dispersal processes, affecting plant communities and ecosystem functions. Even though much information is available on the effects of seed dispersal disruption (SDD), we still lack a comprehensive understanding of its main causes at a global scale, as well as the potential knowledge gaps derived from research biases. Here we review studies of biotic and abiotic seed dispersal disruptions to ascertain the global change drivers addressed, dispersal modes impacted, plant processes affected, and spatial focus of existing research on this topic up-to-date. Although there are many modes of dispersal and global change drivers in temperate and tropical ecosystems worldwide, research efforts have predominantly addressed the effect of alien species for biotic seed dispersal in temperate systems and oceanic islands as well as how defaunation of bird or mammal dispersers has affected seed removal in the Neotropics. SDD studies were also biased towards forest ecosystems, with few in shrublands or grasslands. Finally, the effects of climate change, ecological consequences at the whole community level, and evolutionary changes were largely unrepresented in SDD studies. These trends are likely due to a combination of true geographic and ecological patterns in seed dispersal and global change and bias in research focus. We conclude that increased research investment in the less-studied systems and a better understanding of potential synergies and feedback between multiple global change drivers will be important to forecast the threats to plant biodiversity and ecosystem functions derived from seed dispersal in the Anthropocene.